RT-PCR (Reverse Transcription - Polymerase Chain Reaction): Suatu Cara Pendeteksi Perubahan-Perubahan Ekspresi Gen pada Penyakit - Elza Ibrahim Auerkari; Hari Sunarto; Ariadna Djais (Faculty of Dentistry, Universitas Indonesia, 2015)
The reverse transcription polymerase chain reaction (RT-PCR) is widely applied for detecting mRNA expression and cloning cDNA. This method consists of two parts: cDNA synthesis from mRNA by reverse transcription (RT) and amplification of cDNA by PCR. The RT-PCR has proved useful in amplifying very small amount of specific mRNA to obtain cDNA clones and to detect mRNA transcripts from abnormal cells in a background of normal cells.